Rediscovery and description of the holotype of Oedipus paraensis Unterstein, 1930 (Amphibia, Plethodontidae), and invalidation of the neotype - Gutsche, Alexander; Tillack, Frank; Mahlow, Kristin (Zootaxa, 2017)
It is proposed to invalidate the recently designated neotype for the plethodontid salamander Oedipus paraensis Unterstein, 1930, because the holotype has been rediscovered in the herpetological collection of the Museum für Naturkunde Berlin. As the taxon was recently shown being part of a species complex and the original description of O. paraensis does not provide a clear diagnosis to distinguish it from the other species, we herein supply additional morphometric data of the holotype for comparative purposes.